The effectiveness of Tiger Conservation Landscapes in decreasing deforestation in South Asia: a remote sensing-based study - Sabu, Minu Merin; Pasha, S. Vazeed; Reddy, C. Sudhakar; Singh, Randeep; Jaishanker, R. (Spatial information research (Online), 2022)
The alarming loss of tiger ( Panthera tigris ) populations due to degrading habitat called for an international commitment to double the wild tiger population by 2022 (“Tx2” goal). In the present study, eighteen Priority Tiger Conservation Landscapes (PTCLs) distributed in India, Bangladesh, Bhutan, Nepal and Myanmar were identified to investigate the trends in deforestation and fragmentation in core forest area. We used multi-decadal remote sensing-based maps to assess the rate of deforestation from 1975 to 2016. The time-series analysis revealed that there is a low to moderate level of deforestation reported in PTCLs from 1975 to 2016. The Northern Forest Complex-Namdapha-Royal Manas and Tenasserims are the geographically larger landscapes of the eighteen PTCLs that show the relatively high annual rate of deforestation from 2005 to 2016 due to the practice of shifting cultivation. The Mann Kendall trend test has indicated a statistically significant decreasing trend in deforestation across the 18 PTCLs. Overall, a low level of forest fragmentation was found in core forest habitat in the landscapes from 1995 to 2016. The results indicate management has been effective in minimizing habitat loss. The study outcomes would lead to a holistic understanding at the landscape level for long-term conservation planning in PTCLs.